Fronto-parietal theta high-definition transcranial alternating current stimulation may modulate working memory under postural control conditions in young healthy adults - Xiao, Yanwen; Zhou, Junhong; Zhou, Rong; Liu, Yu; Lü, Jiaojiao; Huang, Lingyan (Frontiers in Human Neuroscience, 2023)
Objects This study aimed to investigate the immediate effects of fronto-parietal θ HD-tACS on a dual task of working memory-postural control. Methods In this within-subject cross-over pilot study, we assessed the effects of 20 min of 6 Hz-tACS targeting both the left dorsolateral prefrontal cortex (lDLPFC) and posterior parietal cortex (PPC) in 20 healthy adults (age: 21.6 ± 1.3 years). During each session, single- and dual-task behavioral tests (working memory single-task, static tandem standing, and a dual-task of working memory-postural control) and closed-eye resting-state EEG were assessed before and immediately after stimulation. Results Within the tACS group, we found a 5.3% significant decrease in working memory response time under the dual-task following tACS (t = −3.157, p = 0.005, Cohen’s d = 0.742); phase synchronization analysis revealed a significant increase in the phase locking value (PLV) of θ band between F3 and P3 after tACS (p = 0.010, Cohen’s d = 0.637). Correlation analyses revealed a significant correlation between increased rs-EEG θ power in the F3 and P3 channels and faster reaction time (r = −0.515, p = 0.02; r = −0.483, p = 0.031, respectively) in the dual-task working memory task after tACS. However, no differences were observed on either upright postural control performance or rs-EEG results (p-values <0.05). Conclusion Fronto-parietal θ HD-tACS has the potential of being a neuromodulatory tool for improving working memory performance in dual-task situations, but its effect on the modulation of concurrently performed postural control tasks requires further investigation.